Histone Acetyltransferases p300 and CBP Coordinate Distinct Chromatin Remodeling Programs in Vascular Smooth Muscle Plasticity. Issue 23 (3rd May 2022) - Chakraborty, Raja; Ostriker, Allison C.; Xie, Yi; Dave, Jui M.; Gamez-Mendez, Ana; Chatterjee, Payel; Abu, Yaw; Valentine, Jake; Lezon-Geyda, Kimberly; Greif, Daniel M.; Schulz, Vincent P.; Gallagher, Patrick G.; et al.
Abstract : Background: Vascular smooth muscle cell (VSMC) phenotypic switching contributes to cardiovascular diseases. Epigenetic regulation is emerging as a key regulatory mechanism, with the methylcytosine dioxygenase TET2 acting as a master regulator of smooth muscle cell phenotype. The histone acetyl-transferases p300 and CREB-binding protein (CBP) are highly homologous and often considered to be interchangeable, and their roles in smooth muscle cell phenotypic regulation are not known. Methods: We assessed the roles of p300 and CBP in human VSMC with knockdown, in inducible smooth muscle–specific knockout mice (inducible knockout [iKO]; p300 iKO or CBP iKO ), and in samples of human intimal hyperplasia. Results: P300, CBP, and histone acetylation were differently regulated in VSMCs undergoing phenotypic switching and in vessel remodeling after vascular injury. Medial p300 expression and activity were repressed by injury, but CBP and histone acetylation were induced in neointima. Knockdown experiments revealed opposing effects of p300 and CBP in the VSMC phenotype: p300 promoted contractile protein expression and inhibited migration, but CBP inhibited contractile genes and enhanced migration. p300 iKO mice exhibited severe intimal hyperplasia after arterial injury compared with controls, whereas CBP iKO mice were entirely protected. In normal aorta, p300 iKO reduced, but CBP iKO enhanced, contractile protein expression and contractility compared with controls. Mechanistically, we found that these histone acetyl-transferases oppositely regulate histone acetylation, DNA hydroxymethylation, and PolII (RNA polymerase II) binding to promoters of differentiation-specific contractile genes. Our data indicate that p300 and TET2 function together, because p300 was required for TET2-dependent hydroxymethylation of contractile promoters, and TET2 was required for p300-dependent acetylation of these loci. TET2 coimmunoprecipitated with p300, and this interaction was enhanced by rapamycin but repressed by platelet-derived growth factor (PDGF) treatment, with p300 promoting TET2 protein stability. CBP did not associate with TET2, but instead facilitated recruitment of histone deacetylases (HDAC2, HDAC5) to contractile protein promoters. Furthermore, CBP inhibited TET2 mRNA levels. Immunostaining of cardiac allograft vasculopathy samples revealed that p300 expression is repressed but CBP is induced in human intimal hyperplasia. Conclusions: This work reveals that p300 and CBP serve nonredundant and opposing functions in VSMC phenotypic switching and coordinately regulate chromatin modifications through distinct functional interactions with TET2 or HDACs. Targeting specific histone acetyl-transferases may hold therapeutic promise for cardiovascular diseases.